LL

Những câu hỏi liên quan
NT
Xem chi tiết
YN
30 tháng 10 2021 lúc 22:25

\(2x^3y-2xy^3-4xy^2-2xy\)

\(=2xy.\left(x^2-y^2-2y-1\right)\)

\(=2xy.[x^2-\left(y^2+2y+1\right)]\)

\(=2xy.[x^2-\left(y+1\right)^2]\)

\(=2xy.\left(x+y+1\right).\left(x-y-1\right)\)

Vậy chọn đáp án A

Bình luận (0)
 Khách vãng lai đã xóa
BA
12 tháng 1 2022 lúc 14:20

chọn A

Bình luận (0)
 Khách vãng lai đã xóa
H24
Xem chi tiết
NH
18 tháng 10 2021 lúc 19:41
Jed7eyeywyeueu3uêuue
Bình luận (0)
 Khách vãng lai đã xóa
NT
18 tháng 10 2021 lúc 19:42

nhìn đề bài rắc rối thế

Bình luận (0)
 Khách vãng lai đã xóa

A=x2−2xy−4x+2y2−8y+20C=x2−2xy−4x+2y2−8y+20

=(x2−2xy+y2)−4(x−y)+4+y2−12y+36−20=(x2−2xy+y2)−4(x−y)+4+y2−12y+36−20

=(x−y)2−4(x−y)+4+(y−6)2−20=(x−y)2−4(x−y)+4+(y−6)2−20

=(x−y−2)2+(y−6)2−20≥−20∀x;y=(x−y−2)2+(y−6)2−20≥−20∀x;y

Dấu " = " xảy ra ⇔{x−y−2=0y−6=0⇔{x−y=2y=6⇔{x−y−2=0y−6=0⇔{x−y=2y=6

⇔x=8;y=6⇔x=8;y=6

Vậy  A là : −20⇔x=8;y=6

Bình luận (0)
 Khách vãng lai đã xóa
TY
Xem chi tiết
BH
9 tháng 11 2016 lúc 12:08

(4x2+2xy+y2)(2x-y)-(2x-y)(4x2-2xy+y2)

=(2x3-y3)-(2x+y)(4x2-2xy+y2)

=(2x3-y3)-(2x3+y3)

=2x3-y3-2x3+y3

=0

Bình luận (0)
US
Xem chi tiết
LL
Xem chi tiết
SM
23 tháng 9 2018 lúc 8:26

( 2x + y ) ( 4x2 - 2xy + y2 ) - ( 2x - y ) ( 4x2 + 2xy + y2 )

= 8x3 + y3 - ( 8x3 - y3 )
= 2y3 

Bình luận (0)
NA
23 tháng 9 2018 lúc 8:42

\(\left(2x+y\right)\left(4x^2-2xy+y^2\right)-\left(2x-y\right)\left(4x^2+2xy+y^2\right)\)

\(=8x^3+y^3-\left(8x^3-y^3\right)\)

\(=8x^3+y^3-8x^3+y^3\)

\(=\left(8x^3-8x^3\right)+\left(y^3+y^3\right)\)

\(=2y^3\)

Bình luận (0)
ET
Xem chi tiết
NM
10 tháng 9 2021 lúc 8:42

Sửa đề \(\left(2x+y\right)\left(4x^2-2xy+y^2\right)-\left(2x-y\right)\left(4x^2+2xy+y^2\right)\)

\(=8x^3+y^3-8x^3+y^3=2y^3\)

Bình luận (0)
NT
10 tháng 9 2021 lúc 8:47

\(\left(2x+y\right)\left(4x^2-2xy+y^2\right)-\left(2x-y\right)\left(4x^2+2xy+y^2\right)\)

\(=8x^3+y^3-8x^3+y^3\)

\(=2y^3\)

Bình luận (0)
LL
Xem chi tiết
KT
9 tháng 7 2018 lúc 20:59

a)  \(A=x^2+2xy+y^2-4x-4y+1\)

\(=\left(x+y\right)^2-4\left(x+y\right)+1\)

\(=3^2-4.3+1=-2\)

b)  \(B=x\left(x+2\right)+y\left(y-2\right)-2xy+37\)

\(=x^2+2x+y^2-2y-2xy+37\)

\(=\left(x-y\right)^2+2\left(x-y\right)+37\)

\(=7^2+2.7+37=100\)

c)  \(C=x^2+4y^2-2x+10+4xy-4y\)

\(=\left(x+2y\right)^2-2\left(x+2y\right)+10\)

\(=5^2-2.5+10=25\)

Bình luận (0)
TB
9 tháng 7 2018 lúc 21:05

a) \(A=x^2+2xy+y^2-4x-4v+1\)

\(=\left(x+y\right)^2-4\left(x+y\right)+1\)

\(=3^2-4.3+1=-2\)

Bình luận (0)
RH
Xem chi tiết
TC
Xem chi tiết
NT
23 tháng 7 2021 lúc 11:34

a) Ta có: \(\left(y+3\right)\left(y^2-3y+9\right)-\left(60-y^3\right)\)

\(=y^3+27-60+y^3\)

\(=2y^3-33\)

b) Ta có: \(\left(2x+y\right)\left(4x^2-2xy+y^2\right)-\left(2x-y\right)\left(4x^2+2xy+y^2\right)\)

\(=8x^3+y^3-8x^3+y^3\)

\(=2y^3\)

Bình luận (0)